An acute gastroenteritis outbreak associated with a contaminated water supply system, Turkey, 2018. (23rd June 2022) - Özgüler, Zeynep Özge; Priyakanta, Nayak; Coban, Serap Cetin; Sezerol, Mehmet Akif; Shaikh, Irshad Ali; Temel, Fehminaz
Abstract: Disruption of routine monitorization and chlorination of the water supply system during a week-long holiday led to a multi-organism gastroenteritis outbreak in a district with limited laboratory support. More than a 10-fold increase in patients with gastroenteritis was reported. Enteropathogenic Escherichia coli, Enteroaggregative E. coli, and norovirus were detected in human specimen samples. The main water tank and pipes were rusted; 13 out of the 19 water samples tested positive for total Coliform (1–920 colony-forming units (CFU)/100 ml) and E. coli (1–720 CFU/100 ml). Chlorine levels were below 0.2 ppm in seven of the nine samples. Information of 1, 815 cases was obtained from the hospital records with a crude attack rate of 2.9%. Cases widespread in the district increased throughout the holiday, epidemic curve revealed a point-source outbreak. The case–control study revealed that consumption of drinking tap water and using it to clean vegetables/fruits were significantly associated with the illness. While drinking only bottled water had a protective effect against the illness. The culture technique showed that the water supply samples were positive for pathogenic bacteria. Upon decision in a multi-stakeholder meeting, the water tank was cleaned, and the Municipality initiated the renovation of the water supply system. HIGHLIGHTS: Disruption of chlorination and infrequent monitoring occurred during a week-long holiday. Water supply samples were tested positive for pathogenic bacteria indicating fecal contamination. Epidemiological investigation aided the rural area with limited health service and laboratory support. Multi-stakeholder intervention was implemented to disinfect and renovate the water supply system. Graphical Abstract